2017
DOI: 10.1186/s13567-017-0446-1
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular delivery of HA1 subunit antigen through attenuated Salmonella Gallinarum act as a bivalent vaccine against fowl typhoid and low pathogenic H5N3 virus

Abstract: Introduction of novel inactivated oil-emulsion vaccines against different strains of prevailing and emerging low pathogenic avian influenza (LPAI) viruses is not an economically viable option for poultry. Engineering attenuated Salmonella Gallinarum (S. Gallinarum) vaccine delivering H5 LPAI antigens can be employed as a bivalent vaccine against fowl typhoid and LPAI viruses, while still offering economic viability and sero-surveillance capacity. In this study, we developed a JOL1814 bivalent vaccine candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Hajam et al used Salmonella to express the HA1 antigen, which has dual functions as a delivery system and as a natural adjuvant, that could trigger specific humoral and cell-mediated immune responses (29). Kamble et al showed that intracellular delivery of HA1 subunit antigens by attenuated Salmonella protected chickens from infection with a low-pathogenicity H5N3 subtype virus and increased systemic viral clearance (30). Our results in the present study are consistent with those reported in other studies; specifically, recombinant Lactobacillus expressing HA1 can induce specific humoral and cellular immunity, indicating that the HA1 antigen can be used as a target-binding antigen for vector delivery with good immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Hajam et al used Salmonella to express the HA1 antigen, which has dual functions as a delivery system and as a natural adjuvant, that could trigger specific humoral and cell-mediated immune responses (29). Kamble et al showed that intracellular delivery of HA1 subunit antigens by attenuated Salmonella protected chickens from infection with a low-pathogenicity H5N3 subtype virus and increased systemic viral clearance (30). Our results in the present study are consistent with those reported in other studies; specifically, recombinant Lactobacillus expressing HA1 can induce specific humoral and cellular immunity, indicating that the HA1 antigen can be used as a target-binding antigen for vector delivery with good immunogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The immunization of chickens with this vaccine candidate demonstrated the faster clearance of H5N3 challenge virus. This recombinant vaccine can be used as a bivalent preparation against fowl typhoid and influenza diseases [28].…”
Section: Recombinant Vector Vaccinesmentioning
confidence: 99%